Visible light active LaFeO3 nano perovskite-RGO-NiO composite for efficient H2 evolution by photocatalytic water splitting and textile dye degradation. Issue 1 (February 2021) - Vijayaraghavan, T.; Althaf, R.; Babu, Pradeepta; Parida, K.M.; Vadivel, S.; Ashok, Anuradha M.
Graphical abstract: Highlights: Novel visible light absorbing, LaFeO3 -RGO-NiO nanocomposites were synthesised. The composite exhibited excellent photocatalytic hydrogen evolution & Congo-red dye degradation. Both RGO and NiO act as co-catalysts for photocatalytic activity. The composites showed consistent photocatalytic activity for several cycles. Abstract: Novel nanocomposites of LaFeO3 (prepared by sol-gel and solid-state method) - Reduced Graphene Oxide (RGO) - NiO were synthesized in an attempt to tune the band gap and band edge potentials to make it suitable for enhanced photocatalytic activity. Crystallographic and morphological studies confirmed the phase purity and revealed the presence of RGO along with LaFeO3 . Optical studies confirmed the higher visible light activity of the material due to narrower bandgap and suitable band edge potentials. The oxidation states and presence of all elements were confirmed by XPS studies. Photocatalytic properties were evaluated by performing hydrogen & oxygen evolution by water splitting and Congo-red dye degradation experiments. The composite prepared by sol-gel method showed better Congo-red dye degradation and higher rate of hydrogen and oxygen evolution without doping any noble metal co-catalyst when compared to the composite prepared by solid-state method under visible light irradiation.